The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.5937/jomb0-27281
|View full text |Cite
|
Sign up to set email alerts
|

Thiol/disulfide homeostasis impaired in patients with primary Sjögren's syndrome

Abstract: Background: Primary Sjögren's syndrome (pSS) is a disease associated with the overexpression of proinflammatory cytokines, and oxidative stress is one of the factors responsible for its etiopathogenesis. This study aimed to investigate the thiol/disulphide homeostasis in pSS patients. Methods: The study included 68 pSS patients and 69 healthy controls. Thiol/disulphide homeostasis (total thiol, native thiol, and disulphide levels) was measured using the automatic spectrophotometric method developed by Erel and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…19,35 Thiol/ disulfide hemostasis has previously been studied in many autoimmune and inflammatory rheumatological diseases (e.g., RA, AS, FMF, and Sjögren's syndrome). 21,24,36,37 Giustarini et al determined that patients with RA had lower thiol and higher disulfide levels than HCs. 23 Tuzcu et al also showed that thiol levels were lower and SS levels were higher in RA patients compared to HCs, and there was a negative correlation between DAS-28 and thiol groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19,35 Thiol/ disulfide hemostasis has previously been studied in many autoimmune and inflammatory rheumatological diseases (e.g., RA, AS, FMF, and Sjögren's syndrome). 21,24,36,37 Giustarini et al determined that patients with RA had lower thiol and higher disulfide levels than HCs. 23 Tuzcu et al also showed that thiol levels were lower and SS levels were higher in RA patients compared to HCs, and there was a negative correlation between DAS-28 and thiol groups.…”
Section: Discussionmentioning
confidence: 99%
“…24 Yilmaz CN et al also showed that thiol decreased in Sjogren's syndrome and the balance shifted to the disulfide side. 37 Baykara RA et al found that there was impaired thiol/ disulfide hemostasis in AS patients and that disease activity was related to the amount of disulfide. 38,39 Similar to all these studies, lower thiol levels and higher SS and SS/thiol ratios were found in SLE patients compared to HCs in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors having direct or indirect impact upon oxidant/antioxidant systems have been involved in pSS etiology. 20 Oxidative stress is considered as the off-balance of free radicals and antioxidants. At low or moderate concentrations, these molecules are essential for some biological processes such as intracellular cell signaling and homeostasis, induction of mitogenic response, immune defense against pathogens, and cell death.…”
Section: Discussionmentioning
confidence: 99%
“…This exposure poses a persistent challenge for maintaining homeostasis, ultimately increasing the risk of oxidative stress [ 5 ]. SjD patients have elevated levels of oxidative stress biomarkers in circulation, conjunctival epithelial cells, minor labial salivary gland biopsy, saliva, serum, and plasma [ 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. These biomarkers are indicative of DNA damage (8-OHdG), lipid peroxidation (HEL and 4-HNE), and protein nitration (nitrotyrosine).…”
Section: Introductionmentioning
confidence: 99%